2020
DOI: 10.32391/ajtes.v4i2.119
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Thoracic Outlet Syndrome Reviewed

Abstract: Neurogenic Thoracic Outlet Syndrome (NTOS) is a rare, but controversial syndrome in relation to its diagnosis, treatment modality, and approaches in case of surgical treatment. In the English literature, there are sparse studies dealing with these aspects. We conducted a PubMed 2000-2017 literature review and found a total of 3953 cases reported with NTOS. The clinical characteristics, etiology, electrophysiological and radiological work-up and treatment options were reviewed and reported. It seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…This rate is higher than many series reported in the literature. The full recovery rate of 78.4% in our study was also in accordance with the success rates of the studies done in our country, but one of the best success rates in the literature belongs to Sanders, who reported a 70% success rate [1,4]. The highest success rate ever reported was by Urschel in his series, at 97%.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This rate is higher than many series reported in the literature. The full recovery rate of 78.4% in our study was also in accordance with the success rates of the studies done in our country, but one of the best success rates in the literature belongs to Sanders, who reported a 70% success rate [1,4]. The highest success rate ever reported was by Urschel in his series, at 97%.…”
Section: Discussionsupporting
confidence: 91%
“…In a long-term study, success rates were reported as 92% for transaxillary intervention, 83% for supraclavicular intervention, and 86% for posterior intervention. Postoperative complication rates do not exceed 4% in the literature [1,2,9,10,16], whereas in our study, the most common complication in 37 cases was pneumothorax, at 14 (37.8%). In contrast to the other series, there was no occurrence of the Horner syndrome, while hemothorax occurred in 2 cases (5.4%) and infection in 1 case (2.7%).…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations